Formation And Characteristics Of Engkabang-Based Nano-Cosmeceuticals - Abd Gani, Siti Salwa (2010)
Engkabang fat esters were synthesized from engkabang fat using Lipozyme® RM IM as a catalyst. The main composition of the fat esters were oleyl palmitate, oleyl stearate and oleyl oleate. The percentage yield was 93.67%. Phase behaviors of engkabang fat and engkabang fat esters were determined through the construction of ternary phase diagrams using nonionic surfactants. The increase of hydrophilic lipophilic balance (HLB) value of the surfactant gave larger homogenous and isotropic region in both ternary phase diagrams of Engkabang fat/Nonionic surfactant/Deionized water and Engkabang fat esters/Nonionic surfactant/Deionized water. Homogenous and isotropic regions were larger in the phase diagrams of engkabang wax esters compared to the phase diagrams of engkabang fat. Compositions of homogenous region from the ternary phase diagrams were selected as a pre-formulated cosmeceuticals emulsions. Then, they were modified with the additions of solubilisant gamma, glycerin, xanthan gum and beeswax in an attempt to get stable formulations at high temperature. Formulations F10 and E15 were chosen for further studies due to the stability at 45˚C. They were prepared using high shear homogenizer, followed by using high pressure homogenizer. Both formulations were stable at room temperature, at 45ºC and after undergoing thaw cycles test. The particle sizes of F10 and E15 after using high pressure were 115.75 nm and 148.41 nm, respectively. The zeta potential of F10 and E15 at 25ºC were -36.4 mV and - 48.8 mV and the pH values were 5.59 and 5.81, respectively. The rheology of F10 and E15 showed pseudoplastic material with shear thinning properties. There were no bacteria and fungus growth in the samples. Short-term moisturizing effect on 20 subjects analyzed by means of Analysis of Variance (ANOVA), gave P-values of 7.35 ×10-12 and 2.77 ×10-15 for F10 and E15, respectively. The hydration of the skins increased after application of F10 and E15 with P-value below 0.05. The formulations of encapsulated and non-encapsulated titanium dioxide using engkabang fat and esters were produced by emulsification method using high shear homogenizer. All the formulations were stable after undergoing thaw cycles test, at room temperature and 45ºC for three months except for Formulations F10-4A and F10-6A. The particle sizes of formulations were range 80 nm to approximately 400 nm. Surface charge measurements of formulations having values from -30 mV to -59 mV denoted the presence of stable dispersions. The morphological characterization confirmed the encapsulations of titanium dioxide in the formulations. The rheology analysis of the formulations showed shear thinning property as when the shear rate increased, the viscosity decreased. Formulations containing Engkabang fat could be classified as the thixotropic materials, whereby formulations containing Engkabang fat esters could be classified as pseudo plastic materials under a non-Newtonian fluid. Increasing amount of TiO2 gave higher pH values of the formulations and higher conductivity. The TGA thermograms showed three major weight losses due to the evaporation of water content, evaporation of water content in lattice structure and decomposition of oil phase. The stable formulations containing encapsulated of TiO2 gave higher absorbance compared to the formulations containing non-encapsulated of TiO2.